STUDI PENGGUNAAN MEDIA PEMBELAJARAN LIVEWIRE TERHADAP HASIL BELAJAR DASAR LISTRIK DAN ELEKTRONIKA - Muhammad Fauzan Hamid; Arif Rahman (JEVTE: Journal of Electrical Vocational Teacher Education, 2022)
Abstract The purpose of this study was to determine the results of learning Basic Electrical and Electronics using Livewire learning media in class X SMK students were significantly different. This research was conducted on students of class X of the Electrical Power Installation Engineering (TITL) program at the Imelda Private Vocational School in Medan in the 2018/2019 Academic Year. The population in this study was the entire class X TITL SMK Private Imelda Medan, with a sample class X-TITL-1 as the experimental class as many as 30 students and X-TITL-2 as the control class as many as 29 students. The method of selecting research samples by finding the level of homogeneity of each class. The process of collecting data using the test method, namely collecting data using an initial test (pre-test) and a final test (post-test) after being given treatment (treatment). To test the normality of the data, the Liliefors test was used at the confidence level (α) = 0.05. The instrument validity test was carried out with content validity and for the test instrument learning outcomes were calculated using the Kuder-Richardsoni formula (KR-20). The data analysis technique used to test the hypothesis is a one-way right-hand t-test with two independent samples.The results showed that the average post-test learning outcomes of Basic Electricity and Electronics in the experimental class was 84.96, which was higher than the control class, which was 77.89. The results of the one-way right-hand t-test also show that the value of tcount > ttable = 5,4005 > 1,672. This means that there is a significant difference in learning outcomes between the experimental class students and the control class students. So it can be concluded that the class of students who are taught using Livewire is better than the learning outcomes of the class of students who are taught without using Livewire learning media. Keywords: Livewire Learning Media, Basic Electrical and Electronics, Learning Outcomes.AbstrakTujuan penelitian ini adalah untuk mengetahui hasil belajar Dasar Listrik dan Elektronika dengan menggunakan media pembelajaran Livewire pada siswa kelas X SMK berbeda secara signifikan. Penelitian ini dilakukan pada siswa kelas X program Teknik Instalasi Tenaga Listrik (TITL) di SMK Swasta Imelda Medan pada Tahun Ajaran 2018/2019. Populasi dalam penelitian ini adalah seluruh kelas X TITL SMK Swasta Imelda Medan, dengan sampel kelas X-TITL-1 sebagai kelas eksperimen sebanyak 30 siswa dan X-TITL-2 sebagai kelas kontrol sebanyak 29 siswa. Metode pemilihan sampel penelitian dengan cara  mencari tingkat homogenitas tiap kelas. Proses pengumpulan data menggunakan metode tes, yaitu pengumpulan data menggunakan tes awal (pre-test) dan tes akhir (post-test) setelah diberikan perlakuan (treatment). Untuk menguji normalitas data digunakan uji liliefors pada taraf kepercayaan (α)= 0,05. Uji validitas instrumen dilakukan dengan validitas isi dan untuk instrumen tes hasil belajar dihitung dengan rumus Kuder-Richardsoni (KR-20). Teknik analisis data yang digunakan untuk menguji hipotesis adalah uji-t satu arah kanan dengan dua sampel independen.Hasil penelitian menunjukkan bahwa rata-rata post-test hasil belajar Dasar Listrik dan Elektronika kelas eksperimen yaitu 84,96 lebih tinggi dibandingkan dengan kelas kontrol yaitu 77,89. Hasil uji-t satu arah kanan juga menunjukkan bahwa nilai thitung > ttabel = 5,4005> 1,672. Artinya ada perbedaan hasil belajar yang signifikan antara siswa kelas eksperimen dengan siswa kelas kontrol. Sehingga dapat disimpulkan kelas siswa yang diajar menggunakn Livewire lebih baik dari hasil belajar kelas siswa yang diajar tanpa menggunakan media pembelajaran Livewire. Kata kunci: Media Pembelajaran Livewire, Dasar Listrik dan Elektronika, Hasil Belajar